Fronteiras entre as dunas : compreendendo a cultura lúdica na Vila de Itaúnas (ES) - Duque, Fernanda Celinga Siqueira (2012)
The purpose of this study is to understand the uses and uses of counter-play culture in Itaúnas (ES) in order to understand the constitution of this town as a place and not place highlighting both moments play culture site. The starting point of understanding culture as a web of meanings historically transmitted that uses symbols as a means of communication between men, perpetuating and expanding their knowledge and their activities toward life (GEETZ, 1989) and in this tangle of meanings can find the play culture, which in turn is the expression of human meanings / culture referenced in playing with oneself, others and the context (GOMES apud GOMES, 2004). Seeking to achieve the purpose of this study, we conducted a survey of memory produced over the place, the story of the play culture of the Village of Itaúnas play culture and how that has been presented today in the lives of villagers in six ethnographic forays into town, with the contribution of the residents who actually lived in the old town, residents and investors who helped build the new village. In addition, we take the concept of play culture to understand behavior patterns which allow you to start the game considering that the practices of fun are an essential part of that society has to tighten its collective bonds and feel united. Given these theoretical assumptions, we combine the data from direct observation in times of foray into the village, the memories of older residents and highly representative, as well as searching for information related to the town in two moments that make up the local culture play: the dance, symbolized by the National Festival of Itaúnas Forro (FENFIT), and the Feasts of Saint Benedict and Saint Sebastian, with presentations of the cultural references. The survey data revealed that in Itaúnas appeared onstage as a diverse and extremely attractive, since the uses established the town as a place. Thus we see that the space of the village of Itaúnas is a different place for those who live or cultural references linked to the activities of the cultural industry forro, a distinct place for those who live in since they were born Itaúnas, for those who left and returned, for those who came to inhabit the village and for those who pass there. Thus, the town of Itaúnas can be considered a space that, when meaning is that many places due to its many possible uses, flows and hybridity that denote the boundaries contained in the local network play culture, alive in the memory of the natives , foreigners and tourists which means the village. So Itaúnas is a place meant by forro, but also meant by the practices of cultural references. Thus, the village consists of two linked, hybridized with its streams, contra-flows, uses and counter-purpose and flexible boundaries, permeated by political and social issues involved in the Village of Itaúnas.